2017
DOI: 10.1002/adfm.201606842
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polymeric Metal Nucleation Inducers in Fabricating Large‐Area, Flexible, and Transparent Electrodes for Printable Electronics

Abstract: The advent of special types of transparent electrodes, known as "ultrathin metal electrodes," opens a new avenue for flexible and printable electronics based on their excellent optical transparency in the visible range while maintaining their intrinsic high electrical conductivity and mechanical flexibility. In this new electrode architecture, introducing metal nucleation inducers (MNIs) on flexible plastic substrates is a key concept to form high-quality ultrathin metal films (thickness ≈ 10 nm) with smooth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…The pink layer denotes the CBL composed of ZrAcac, PEI, or ZrAcac/PEI (Figure b), which was spin‐coated on the underlying PCBM film using the optimal concentration of ZrAcac (1 mg mL −1 ) and PEI (0.1 mg mL −1 ) solutions with isopropanol (IPA) as solvent . The main motivation for the use of PEI is that this polymer molecule acts as a good substrate for deposition of smooth silver films . The function of CBL at the cathode interface is clearly demonstrated in the current density–bias voltage ( J–V ) curves in reverse scan of the devices tested under a simulated AM1.5G sunlight (100 mW cm −2 ) (Figure c).…”
Section: Summary Of the Photovoltaic Performances Of The Inverted Plamentioning
confidence: 99%
See 1 more Smart Citation
“…The pink layer denotes the CBL composed of ZrAcac, PEI, or ZrAcac/PEI (Figure b), which was spin‐coated on the underlying PCBM film using the optimal concentration of ZrAcac (1 mg mL −1 ) and PEI (0.1 mg mL −1 ) solutions with isopropanol (IPA) as solvent . The main motivation for the use of PEI is that this polymer molecule acts as a good substrate for deposition of smooth silver films . The function of CBL at the cathode interface is clearly demonstrated in the current density–bias voltage ( J–V ) curves in reverse scan of the devices tested under a simulated AM1.5G sunlight (100 mW cm −2 ) (Figure c).…”
Section: Summary Of the Photovoltaic Performances Of The Inverted Plamentioning
confidence: 99%
“…The silver grains in both kinds of films are well connected with each other (Figure f,h), which contribute to the high conductivity and transmittance shown in Figure a,c. Different from PCBM and ZrAcac, the abundant amine groups in the backbone of PEI molecules are inclined to uniformly localize Ag adatoms by the AgN bonds and hence to offer the low energy nucleation sites for the growth of continuous silver films …”
Section: Summary Of the Photovoltaic Performances Of The Inverted Plamentioning
confidence: 99%
“…1c(i) and (ii)), or PET modified with an ultra-thin layer of PEI (polyethylenimine) the latter of which is known to serve as an effective seed layer for evaporated Ag film. 16 The substrate was then exposed to Ag vapour in a vacuum evaporator until a total thickness of 90 nm was deposited onto PFDMA-free regions and the adjacent quartz crystal microbalance ( Fig. 1c(iii)).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the structures of Ag films so deposited are still far from being ideal and consist of rough surfaces with high densities of voids and grain boundaries when the film thickness is < 6 nm. Recently, it was demonstrated that the density of the sites that are chemically reactive with the evaporated Ag atoms could be determined by the concentration of functional amine groups on the NISL surface (Jeong et al, 2017). However, the adsorbed amine groups in the PEI NISL is always limited by the poor electrostatic attraction to the weakly charged substrate as well as the strong repulsion between the PEI chain entanglements (Hoogeveen et al, 1996;Li et al, 1997;Dobrynin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%